Parallel driving in CPSS: a unified approach for transport automation and vehicle intelligence - Wang, Fei-Yue; Zheng, Nanning; Cao, Dongpu; Martinez, Clara Marina; Li, Li; Liu, Teng (IEEE, 2017)
The emerging development of connected and automated vehicles imposes a significant challenge on current vehicle control and transportation systems. This paper proposes a novel unified approach, Parallel Driving, a cloud-based cyberphysical-social systems U+0028 CPSS U+0029 framework aiming at synergizing connected automated driving. This study first introduces the CPSS and ACP-based intelligent machine systems. Then the parallel driving is proposed in the cyber-physical-social space, considering interactions among vehicles, human drivers, and information. Within the framework, parallel testing, parallel learning and parallel reinforcement learning are developed and concisely reviewed. Development on intelligent horizon U+0028 iHorizon U+0028 and its applications are also presented towards parallel horizon. The proposed parallel driving offers an ample solution for achieving a smooth, safe and efficient cooperation among connected automated vehicles with different levels of automation in future road transportation systems.
Keywords: Automation; Vehicles; Testing; Trajectory; Learning (artificial intelligence); Road transportation